Seroprevalence and Risk Factors of Brucellosis in Ruminants in Dhofar Province in Southern Oman - Waleed Al-Marzooqi; Elshafie I. Elshafie; AlGhalya Al-Toobi; Abeer Al-Hamrashdi; Kaadhia Al-Kharousi; Hatim El-Tahir; Maryne Jay; Yannick Corde; Yasmin ElTahir (Veterinary Medicine International)
Objective. The aim of the present work was to raise awareness of Brucella infection and emphasize the use of serological tests for screening and confirmation of the presence of the infection in different localities in the Dhofar region in the Sultanate of Oman. Methods. A seroprevalence of Brucella infection in naturally infected livestock was undertaken in 50 farms (a total of 434 sera, 207 goats, 84 sheep, 54 cattle, and 89 camels) from different wilayat of the Dhofar region in the southern part of Oman. Rose Bengal (RBT), complement fixation (CFT), and indirect enzyme-linked immunosorbent assay (I-ELISA) tests were used to determine the presence of Brucella antibodies. Statistical analysis (Pearson chi-square, binary logistic regression, and univariate logistic regression) was used to investigate the significance between the prevalence and the categorical risk factors individually, with two or more levels (animal species, animal condition, and or location). Results. Our results show that the overall seroprevalence based on CFT, RBT, and I-ELISA was 3% (13/424, CI: 1.8–5.1%), 4.8% (21/434, CI: 3.1–7.3%), and 8% (35/434, CI: 5.8–10.9%), respectively. The highest seroprevalence was reported in goats (13% (27/207)) and animals from East Jabal (13% (21/161)), whereas the lowest was recorded in camels (3.4% (3/89)) and animals from deserts (1.4% (1/69)). Parameters such as the positive predictive value (PPV) and the negative predictive value (NPV) showed that the sensitivity of I-ELISA and CFT based on the RBT test was 61.9% and 57.1%, respectively, whereas the specificity of I-ELISA (94.6%) was less than that of CFT (97.33%). Conclusion. We concluded that three tests are confirmatory for the presence of Brucella infection.